Rasionalitas Agama Menurut Muhammad Abduh - Muhim Nailul Ulya (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2017)
The study in this paper describes the rationality of Muhammad Abduh insome of his works by going to take some samples of religious domains thatgenerate a lot of polemics, both among Muslims themselves, philosophersand theologians, as well as outside Muslims, the orientalists.Muhammad Abduh was greatly influenced by Jamal ud-Din al-Afghani, thefounder of the modern pan-Islamic movement which sought to unite theMuslim world under the banner of the faith. When they met in al-Azhar in1872 Abduh was roused from his asceticism to activism and sought to bringabout a renaissance of Islam and a liberation of Muslims from colonialism.Unlike his mentor, Jamal ud-Din al-Afghani, Abduh tried to separate politicsfrom religious reform. Abduh advocated the reform of Islam by bringing itback to its pristine state and casting off what he viewed as its contemporarydecadence and division. His views were opposed by the established politicaland religious order, but were later embraced by Arab nationalism afterWorld War I.